A formação e desenvolvimento de conceitos e atenção voluntária de crianças em experimento pedagógico de intervenção com jogos na Educação Física - Ayoub, Ronan Ahmad Juste (Universidade Federal de São Carlos, 2025)
This research investigated the instruments and methodological procedures necessary for the development of the higher psychological functions of voluntary attention and the formation of scientific concepts in six-year-old children during Physical Education classes. This study was supported by Historical-Cultural Theory, which postulates that human development is shaped by social interactions, language, and the appropriation of culture in a given historical context. The theory's principles are: the development of the human mind through the appropriation of historically constituted social forms of human activity, effective activity appropriate to the individual, and the development of higher psychological functions that foster self-control and self-mastery. The research aimed: to develop instruments and methodological procedures inherent to the development of the psychological functions of voluntary attention and the formation of scientific concepts, using social role-playing and table/board games; to develop a pedagogical intervention experiment based on the learning needs of the target people; and to discuss the effectiveness of the methodological instrument applied. They used the following methodological instruments: a pedagogical intervention experiment with systematic and participant observation and structured activities aligned with the fundamentals of Historical-Cultural Theory; activities consisting of body tracking and board tracking, human chess and board chess, laterality games, and social role games, to promote social interaction. For systematic observations, we used video recordings and a field diary. The results showed that, in the pedagogical intervention experiment, the integration of bodily experiences and symbolic games favored the development of voluntary attention and scientific concepts, especially when they are mediated by language and conscious action. We emphasize the role of "affinity groups" in organizing relationships among students, which required intentionality on the part of the researcher to foster meaningful mediating activities for learning. The results also showed that the transposition from the concrete to the abstract proved effective, especially when it is anchored in bodily experience. We concluded that intentional pedagogical environments, structured with social role-playing and table/board games, significantly favored the development of voluntary attention and the formation of scientific concepts in six-year-old children. Planned teacher mediation, based on the Action Guiding Framework and levels of assistance, proved effective in promoting the conscious and autonomous internalization of learning, reaffirming the principles of Historical-Cultural Theory and contributing with new perspectives to pedagogical practice in Physical Education.
The formation and development of concepts and voluntary attention in children through a pedagogical intervention experiment with games in Physical Education
Keywords: Teoria histórico-cultural; Desenvolvimento de conceitos; Atenção voluntária; Experimento pedagógico de intervenção; Educação Física; Historical-cultural theory; Concept development; Voluntary attention; Pedagogical intervention experimente; Physical Education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM